IMPLEMENTING DEEP LEARNING BASED LEARNING MANAGEMENT TO IMPROVE LEARNING QUALITY AT SD IT ULUL ALBAB 2 PURWOREJO - Nurhidayati Nurhidayati; Titi Anjarini; Ma’rifat Nur Adeli; Dufiana Tofani; Basuki Basuki (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Improving learning quality in Islamic elementary schools requires management strategies that are both pedagogically strong and sensitive to the school’s religious identity. This study examines how deep learning based learning management is applied at SD IT Ulul Albab 2 Purworejo Regency using a descriptive qualitative design supported by observations, informal teacher interviews, and document analysis. Deep learning is understood as an approach that emphasizes conceptual understanding, inquiry, collaboration, reflection, and the integration of Islamic character values. The thematic analysis, supported by triangulated data sources, shows that the school implements this framework through contextual curriculum planning, active collaborative learning, value-based routines, and authentic assessment practices. While not making causal claims, the findings reveal emerging indications of increased student engagement, stronger critical thinking tendencies, and the reinforcement of Islamic behavior. Overall, the study suggests that deep learning based learning management offers a promising model for Islamic integrated schools seeking to enhance educational quality and nurture Qur’anic and 21st century competencies.